2023
DOI: 10.1177/20427530231153944
|View full text |Cite
|
Sign up to set email alerts
|

Opportunity in COVID-19 crisis: Moving away from chalk and talk to technology-integrated teaching in Nepalese higher education institutions

Abstract: This qualitative study explored teachers’ use of technology to manage teaching and learning activities during COVID-19 in Nepalese higher education institutions. To this end, 11 teachers from three universities located in five provinces of Nepal were purposefully selected. Their experiences of using technological tools were explored through semi-structured interviews and document analysis. The findings show that the implementations of online teaching and learning to manage students’ learning loss during the CO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 30 publications
0
0
0
Order By: Relevance
“…However, both the teachers and students were found to have taken as the opportunity to practice e-pedagogy in e-classes. In this regard, Thapaliya, Adhikari and Rana (2023) further support from their research findings that the teachers have taken the COVID-19 crisis as an opportunity for learning to use technologies in their teaching and learning activities, though they were marred by paradoxical policy, insufficient resources, teachers' attitudes, socio-psychological issues, the lack of trained teachers and connection among technology, curriculum, pedagogy and assessment. In the same vain, Khanal (2020) also suggests for ensuring the access of ICT resources and facilities to both teachers and students, sufficient training to the both groups and digitalize curricular materials for the effective implementation of virtual learning (p. 89).…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…However, both the teachers and students were found to have taken as the opportunity to practice e-pedagogy in e-classes. In this regard, Thapaliya, Adhikari and Rana (2023) further support from their research findings that the teachers have taken the COVID-19 crisis as an opportunity for learning to use technologies in their teaching and learning activities, though they were marred by paradoxical policy, insufficient resources, teachers' attitudes, socio-psychological issues, the lack of trained teachers and connection among technology, curriculum, pedagogy and assessment. In the same vain, Khanal (2020) also suggests for ensuring the access of ICT resources and facilities to both teachers and students, sufficient training to the both groups and digitalize curricular materials for the effective implementation of virtual learning (p. 89).…”
Section: Discussionmentioning
confidence: 85%
“…Moreover, the findings suggest that if invested in infrastructure development and lecturers' professional development, the universities can gradually adopt online learning as an alternative mode of learning to provide equal access to quality education for all (ibid). Critically arguing the practices of use of e-pedagogy, Thapaliya, Adhikari, and Rana (2023) claimed that the implementations of online teaching and learning to manage students' learning loss during the COVID-19 were marred by paradoxical policy, insufficient resources, teachers' attitudes, socio-psychological issues, the lack of trained teachers and connection among technology, curriculum, pedagogy and assessment. Interestingly, they further supported the use of e-pedagogy that the teachers have taken the COVID-19 crisis as an opportunity for learning to use technologies in their teaching and learning activities.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Despite having positive attitudes towards distance learning, they acknowledged that some difficulties would make it necessary to integrate online learning during the pandemic completely. A shortage of required equipment, particularly digital devices, fast and reliable technical assistance and high-speed internet access, were some to mention (Erlam et al, 2021;Pather et al, 2020;Thapaliya et al, 2023). Similarly, inadequate professional development opportunities regarding the use of technology are another barrier to using online education (Album & Ahmed, 2015;Hamel et al, 2013), as research participants acknowledged the need for professional development training to adopt online teaching efficiently.…”
Section: Discussionmentioning
confidence: 99%
“…Thapaliya et al (2023) found that the COVID-19 directly impacted lecturers' social-physical and psychological health. As consequences, students and teachers required personal counselling on reducing stress and anxieties (Thapaliya et al, 2023).…”
Section: Lecturers' and Students' Socio-psychological Issuesmentioning
confidence: 98%
See 1 more Smart Citation